INFLUENCE OF LABOR DISCIPLINE ON ECONOMIC EFFICIENCY IN THE ACTIVITY OF ENTERPRISES (Marketing Journal, 2025)
“Work discipline in an enterprise is a set of transmission functions that actively motivate from the perspective of microeconomic management theory,” says Nobel laureate and international expert on labor discipline Claudia Goldin. The Chicago School of Eco nomics has also conducted several experimental trials to improve labor discipline, achieving 97.6% economic efficiency and increasing diversification by 69%. This article presents institutional research on the impact of labor discipline on the economic eff iciency of enterprises.
Keywords: macroeconomic crisis; market equilibrium; management art; psychological management; labor market; diversification. 171